The Valley of Fear - Doyle, Arthur Conan, 1859-1930; Adapted by Flynn, Adrian (Oxford, Pakistan Oxford University Press, 2016)
In 'The Valley of Fear', Sherlock Holmes once again matches wits with the most brilliant criminal mastermind of all time, Professor James Moriarty. Holmes and Watson receive a coded message that leads them to a murder in a castle and an adventure that will range half way around the world.
Include Illustration
Keywords: Holmes, Sherlock -- England -- Private investigators